Five practical strategies to get a grip on large group cooperative virtual learning in medical education - Peters, Ryan; Wijeratne, Neshaya; Bowman, Meghan; Wijeratne, Don Thiwanka (Canadian Medical Education Journal, 2023)
The COVID-19 pandemic has led to the rapid replacement of in-person classroom learning with virtual large group learning. Done well, virtual large group learning can be an effective tool that provides flexibility, accessibility, and collaboration between learners. However, despite its potential benefits, human and technological challenges limit engagement and overall efficacy of large group virtual learning. The following account provides an evidence-based framework to maximize cooperative learning, learner engagement and retention of medical education in the virtual setting.